Minimally invasive surgery for hip fracture. Case Report - Lázaro Martínez Aparicio; Lázaro Martín Martínez Estupiñán; Luis Alberto Lugo Pijuan (Acta Médica del Centro, 2021)
Introduction: the presentation of this case provides a new vision of how to address one of the most common traumatic diseases of the elderly in Cuba. Case report: a 77 year-old elderly patient is presented with a fall. On physical examination, shortening, abduction and external rotation of the lower limb were found, then hip fracture was diagnosed. The patient stated that, for religious reasons, she did not wish to be transfused if necessary; fixation with a plate and screws was indicated. It was decided to perform minimally invasive surgery. Conclusions: minimally invasive techniques can be considered for hip fracture surgery in order to save blood and achieve less exposure, minor scarring, lower morbidity and fewer complications.